Perspektif Nilai-nilai Kemanusiaan dalam Baiat Aqabah dan Piagam Madinah - Hasbulloh Huda, Muhammad; Hasyim, Muhammad (LPPI Universitas Al-Qolam Malang, 2020)
Since the beginning of the growth of Islam brought by the Prophet Muhammad, human values have always been urgent matters which have been strived to always be manifested in human life at that time. The manifestation of these human values can be found in several important events during the time when the Prophet Muhammad preached Islam to the Aus and Khazraj of Yathrib. Likewise, when Rasulullah SAW became the highest leader in Medina, in his efforts to regulate the life of the people of Medina at that time.